Rethinking the choice of carbon tax and carbon trading in China - Jia, Zhijie; Lin, Boqiang (Technological forecasting & social change, 2020)
•Carbon tax on energy production industry increases energy supply cost, and carbon trading increases energy demand cost.•Carbon tax directly reduces energy production and indirectly reduces CO2 emissions via international and domestic trade.•Carbon trading directly reduces the carbon emissions of covered industries, but has limited impact on other industries.•In the long run, the emission reduction capacity of carbon tax is slightly greater than that of carbon trading mechanism. Carbon tax and carbon emission trading are used as emission reduction strategies. This paper re-analyzes the differences between the carbon tax and carbon trading by applying a recursive dynamic computable general equilibrium model, called the CEEEA (China Environmental-Energy-Economy Analysis) model. Unlike previous literature, we make the gross domestic product an exogenous variable and explore different effects between carbon tax mechanism and carbon trading mechanism on the environment, energy, and economy. Given a constant GDP effect, both carbon trading and carbon tax have strong emission reduction capacity, but the relative emission reduction efficiency of the carbon tax is higher than that of carbon trading. This advantage increases over time. Carbon trading has a certain negative effect on the output of the energy industry, and also on the output of other energy-intensive industries involving in carbon trading. After considering the various invisible costs of establishing a new carbon trading market, this paper recommends that China could directly levy a carbon tax on energy enterprises, or just increase the production tax on fossil fuels to reduce CO2 emissions effectively. In this way, the commodity market can be used for price incentives and thus, achieve the goal of emission reduction.